Bioactive Components from Ampelopsis japonica with Antioxidant, Anti-α-Glucosidase, and Antiacetylcholinesterase Activities - Jia-Hua Liang; Hsiang-Ru Lin; Chang-Syun Yang; Chia-Ching Liaw; I-Chou Wang; Jih-Jung Chen (MDPI AG, 2022)
The dried root of Ampelopsis japonica (Thunb.) Makino (A. japonica.) is a traditional medicine used to treat fever, pain, and wound healing. It exhibits anti-inflammatory, antitumor, antityrosinase, and antimelanogenic activities. In this paper, we used different solvent extracts from the root of A. japonica to determine their antioxidant activity. Acetone extract showed relatively strong antioxidant properties by 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-(2,4,6-trinitrophenyl)hydrazyl (DPPH), superoxide radical scavenging activity, and ferric reducing antioxidant power (FRAP) assays. In addition, these extracts also showed significant α-glucosidase and acetylcholinesterase (AChE) inhibitory activities. Acetone extract significantly inhibited α-glucosidase with an IC50 value of 8.30 ± 0.78 μg/mL, and ethanol extract remarkably inhibited AChE with an IC50 value of 37.08 ± 7.67 μg/mL. Using HPLC analysis and comparison with the chemical composition of various solvent extracts, we isolated seven active compounds and assessed their antioxidant, anti-α-glucosidase, and anti-AChE activities. Catechin (1), gallic acid (2), kaempferol (3), quercetin (4), resveratrol (6), and epicatechin (7) were the main antioxidant components in the root of A. japonica. According to the results of DPPH, ABTS, and superoxide radical scavenging assays, these isolates showed stronger antioxidant capacity than butylated hydroxytoluene (BHT). Moreover, 1, 3, 4, euscaphic acid (5), 6, and 7 also expressed stronger anti-α-glucosidase activity than the positive control acarbose, and all the isolated compounds had a good inhibitory effect on AChE. Molecular docking models and hydrophilic interactive modes for AChE assays suggest that 1 and 5 exhibit unique anti-AChE potency. This study indicates that A. japonica and its active extracts and components may be a promising source of natural antioxidants, α-glucosidase, and AChE inhibitors.